The Prospect of Local Wisdom Based Village Tourism Through the Perspective of Sharia Economy - Sakinatul Rahmi; Nurul Inayah; Nurul Jannah (LAA MAISYIR : Jurnal Ekonomi Islam, 2025)
Rural poverty in remote areas is often driven by geographical isolation, traditional economic structures, and the underutilization of local potential. Singkuang Village, located in Muara Batang Gadis District, Mandailing Natal Regency, possesses village tourism potential based on local wisdom that has not been optimally developed. This study aims to analyze the potential of local wisdom–based village tourism from the perspective of Islamic economics as a strategy for community economic empowerment. This research employs a qualitative approach, with data collected through direct observation, literature review, and in-depth interviews with village officials, tourism managers, local communities, and the Village Community Empowerment Office. The results indicate that the development of Batu Badaun Beach tourism has contributed to increasing economic independence among local residents, particularly fishermen, through community-based economic activities. Local wisdom reflected in traditional products, rural architecture, and cultural practices supports the development of a creative economy aligned with Islamic economic principles, including justice, empowerment, and sustainability. The novelty of this study lies in integrating local wisdom–based tourism development with an Islamic economic perspective, demonstrating its relevance as an effective poverty alleviation model and positioning Singkuang Village as a potential pilot village for sustainable rural tourism development.